The Structures of Virtue and Vice - Daly, Daniel J. (Professor of moral theology) (Book collections on Project MUSE., 2021)
Daly uses the lens of virtue and vice to reimagine a Catholic ethics that can scrutinize the social forces that both affect our moral character and contribute to human well-being or suffering, creating an ethical framework for responding virtuously to the problems caused by global social systems.